Hyperlipidemia, Hypercholesterolemia and Glycemic Control as Risk Factor for Diabetic Retinopathy (Medical Forum Monthly, 2024)
Objective: To investigate the blood lipids, serum cholesterol and glycaemic control as risk factor for Diabetic retinopathy (DR).Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Muhammad Medical College Hospital Mirpurkhas and Consultant Clinics Hyderabad from March 2014 to January 2015.Materials and Methods: 100 cases of DR were selected for present study. Fundoscopy was performed by the physician followed by a Consultant ophthalmologist. Blood was collected from peripheral vein after a fasting state of 8 – 12 hours. Glycated hemoglobin A1 (A1C) and lipids were evaluated by standard assays. Volunteers were requested to sign to informed consent profroma. Research topic was approved by ethics committee of institute. Statistix 8.1 for data analysis and P-value ≤0.05 was considered significant.Results: Of 100 patients, 58 (58%) were male and 42 (42%) were female patients. Mean ± SD age in patients with and without DR was 49.5±8.5 and 46.3±5.1 years respectively. 21% frequency was noted for DR of any type. Age, male, A1C, hypercholesterolemia, hyperlipidemia and microalbuminuria proved positive correlated with DR. Correlation of DR was not found with VLDL, HDLc and triacylglycerolsConclusion: The present study reports hyperlipidemia, hypercholesterolemia and poor glycaemic control as risk factors for diabetic retinopathy.